SISTEM INFORMASI PENCARIAN JUDUL SKRIPSI TEKNIK INFORMATIKA BERBASIS WEB (STUDI KASUS PRODI TI UNIVERSITAS PAMULANG) - Sandi Hartawan; Fitri Yanti (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
Often students have difficulty in finding the theme of the thesis title and the final project and get into trouble by several times changing the thesis title and the final project. Submission of titles is sometimes accepted and sometimes rejected based on considerations, one of which is an existing title. The goal of the study was to create software that could search and check thesis titles and final tasks quickly and accurately. The method used in this research is the development method that is how the system is developed from a manual system to a computerized system. With this information system application, it is expected to facilitate checking, searching and managing thesis titles and student final assignments and avoid indications of similar titles and plagiarism.